Competencias Del Alumnado Formado En La Escuela De Formación De Profesorado: Una Investigación Reflexiva En El Contexto De Formación Inicial Docente - Da Silva, Maria Do Céu Pereira Antunes; Marín, José Antonio Marín; Artacho, Esther Garzón (European Scientific Journal, ESJ, 2017)
This work was supported by the teaching practice. In it, we try to reflect on the output profile of the graduate student Teacher Training College. The article presented here includes a summary of the relevant aspects collected from a descriptive study, by applying a questionnaire to the student trainees. We conducted interviews with the governing body and some teachers. In order to talk about the profile it was necessary to analyse carefully the beliefs, opinions and performance of teaching, based on the following issue: will the students trained in Teacher Training College have an ideal output profile capable of exercise with pedagogical mastery the teaching profession? We have formulated the following general and specific objectives. General: To reflect on the output profile and the needs of the training offer that graduate students from T.T.C receive in terms of quality, skills, adaptation, and the different requirements on the models required by the Ministry of Education.